Molecular architectures of self-assembling peptides for combating resistant bacteria - Cesar Augusto Roque-Borda; Waleska Stephanie da Cruz Nizer; Subham Kumar Vishwakarma; Oswaldo Julio Ramirez Delgado; Zidane Qriouet; Andréia B. Meneguin; Fernando Rogério Pavan (Chemical Engineering Journal, 2026)

Ag(I) complexes with natural products and triphenylphosphine: activity against tumor cell lines and mycobacterium tuberculosis - Jocely Lucena Dutra; João Honorato de Araujo-Neto; Rafael Wendel Rodrigues Santana; Rone Aparecido De Grandis; Giulia Polinário; Fernando Rogério Pavan; Javier Ellena; Alzir Azevedo Batista (JBIC Journal of Biological Inorganic Chemistry, 2026)

Solidification/stabilization of metallurgical tailings from the zinc process: environmental, microstructural, and mechanical aspects - Fernando Fante; Andrés Lotero; Hugo Carlos Scheuermann Filho; Giovani Jordi Bruschi; Maiki Mafessoli; Maria Alice Piovesan; Paulo Henrique Nogueira Metzker; Eduardo Pavan Korf; Nilo Cesar Consoli (Environmental Science and Pollution Research, 2026)
The management of metallurgical tailings from the zinc process (MTZP) involves a series of hazards due to the presence of heavy metals and sulfates in its composition. An alternative to overcome these difficulties is the use of the solidification/stabilization technique associated with the disposal in dry stacks. For this purpose, it was evaluated the environmental, microstructural, and mechanical properties of compacted metallurgical tailings from the zinc process stabilized with quicklime, Portland cement, and a mixture of both to reduce the potential contamination and increase the mechanical properties, under 7 and 28 days of curing. Analyses such as X-ray fluorescence spectrometry, X-ray diffraction, Fourier transform infrared spectroscopy, and scanning electron microscopy were conducted. Complementarily, mechanical response (unconfined strength and initial shear modulus) and batch leaching tests were executed to provide a complete understanding of treated material behavior. Stabilization with Portland cement reduced the leaching of heavy metals and was not effective in stabilizing the sulfates. The quicklime, due to the common ion effect, provided a reduction in the leaching of sulfates and some heavy metals and a better mechanical response compared to Portland cement. The use of both stabilizers produced the best combination of encapsulation of heavy metals, reduction in the leaching of sulfates, and enhancement of the mechanical properties.

Beet leaves after in vitro human gastrointestinal digestion present antioxidant capacity and protective effects in colorectal cancer cells - Luis Gustavo Saboia Ponte; Beatriz Terui Milanezi; Izabella Batista Barbosa; Isadora Carolina Betim Pavan; Ana Paula Morelli; Mariana Camargo Silva Mancini; Luiz Guilherme Salvino da Silva; Jessica Freire Feitor; Aline Teixeira do Brasil Morais; Daniel Rodrigues Cardoso; Maria Teresa Bertoldo Pacheco; Adriane Elisabete Costa Antunes; et al. (Food Research International, 2025)

Alginate-pectin microparticles embedding self-assembling antimicrobial peptides and resveratrol for antimicrobial and anti-inflammatory applications - Cesar Augusto Roque-Borda; Marco Roberto Chávez-Morán; Laura Maria Duran Gleriani Primo; José C.E. Márquez Montesinos; Vinicius Martinho Borges Cardoso; Mauro M.S. Saraiva; Caroline Maria Marcos; Marlus Chorilli; Fernando Albericio; Beatriz G. de la Torre; Fernando Rogério Pavan; Andréia Bagliotti Meneguin (Food Hydrocolloids, 2025)

Nanofiber-boosted retrograded starch/pectin microparticles for targeted 5-Aminosalicylic acid delivery in inflammatory bowel disease: In vitro and in vivo non-toxicity evaluation - Andréia Bagliotti Meneguin; Cesar Augusto Roque-Borda; Ana Beatriz Grotto Piperas; Maria Fernanda Ortolani Pollini; Vinicius Martinho Borges Cardoso; Laura Maria Duran Gleriani Primo; Forogh Alemi; Fernando Rogério Pavan; Marlus Chorilli (Carbohydrate Polymers, 2024)

Antimicrobial peptides grafted onto the surface of N-acetylcysteine-chitosan nanoparticles can revitalize drugs against clinical isolates of Mycobacterium tuberculosis - Laura Maria Duran Gleriani Primo; Cesar Augusto Roque-Borda; Christian Shleider Carnero Canales; Icaro Putinhon Caruso; Isabella Ottenio de Lourenço; Vitória Maria Medalha Colturato; Rafael Miguel Sábio; Fernando Alves de Melo; Eduardo Festozo Vicente; Marlus Chorilli; Hernane da Silva Barud; Paula Aboud Barbugli; et al. (Carbohydrate Polymers, 2024)

Structural and morphological properties of in-situ biosynthesis of biocompatible bacterial cellulose/Laponite nanocomposites - Rafael R. Domeneguetti; Vanessa Y. Sakai; Gustavo F. Perotti; Isabel C. Silva; Agnieszka Tercjak; Hernane S. Barud; Fernando Pavan; Vera R.L. Constantino; Sidney J. Ribeiro (Applied Clay Science, 2023)

Integrated analysis reveals a new species of Corydoras Lacépède, 1803 (Siluriformes: Callichthyidae) in the lower Iguassu River, Brazil - Rafael Henrique da Rocha; Carlos Alexandre Fernandes; Thaís Souto Bignotto; Vladimir Pavan Margarido; Luiz Fernando Caserta Tencatt; Weferson Júnio da Graça; Éder André Gubiani (Organisms Diversity & Evolution, 2022)

Mucoadhesive In Situ Gelling Liquid Crystalline Precursor System to Improve the Vaginal Administration of Drugs - Patricia Rocha de Araújo; Giovana Maria Fioramonti Calixto; Isabel Cristiane da Silva; Lucas Henrique de Paula Zago; João Augusto Oshiro Junior; Fernando Rogério Pavan; Anderson Orzari Ribeiro; Carla Raquel Fontana; Marlus Chorilli (AAPS PharmSciTech, 2019)

Characterization and complete genome sequence of groundnut ringspot orthotospovirus in soybean in Brazil - Bruno Rossitto De Marchi; Vinicius Henrique Bello; Luis Fernando Maranho Watanabe; Felipe Barreto da Silva; Cristiane Müller; Marcelo Agenor Pavan; Renate Krause-Sakate (Journal of Plant Pathology, 2019)

Evidence for increased efficiency of virus transmission by populations of Mediterranean species of Bemisia tabaci with high Hamiltonella prevalence - Vinicius Henrique Bello; Luís Fernando Maranho Watanabe; Beatriz Rosa Santos; Julio Massaharu Marubayashi; Valdir Atsushi Yuki; Bruno Rossitto De Marchi; Marcelo Agenor Pavan; Renate Krause-Sakate (Phytoparasitica, 2019)

Determination of in vitro absorption in Caco-2 monolayers of anticancer Ru(II)-based complexes acting as dual human topoisomerase and PARP inhibitors - Mariana S. de Camargo; Rone A. De Grandis; Monize M. da Silva; Patricia B. da Silva; Mariana M. Santoni; Carlos E. Eismann; Amauri A. Menegário; Marcia R. Cominetti; Cleslei F. Zanelli; Fernando R. Pavan; Alzir A. Batista (BioMetals, 2019)

First report of tomato severe rugose virus in eggplant - Mônika Fecury Moura; Rafaela Gomes Ruschel; Guilherme Augusto Gotardi; Luís Fernando Maranho Watanabe; Camila Moraes Rêgo; Alice Kazuko Inoue-Nagata; Marcelo Agenor Pavan; Jorge Alberto Marques Rezende; Renate Krause-Sakate (Journal of Plant Pathology, 2018)

Human topoisomerase inhibition and DNA/BSA binding of Ru(II)–SCAR complexes as potential anticancer candidates for oral application - Rone A. De Grandis; Mariana S. de Camargo; Monize M. da Silva; Érica O. Lopes; Elias C. Padilha; Flávia A. Resende; Rosângela G. Peccinini; Fernando R. Pavan; Alessandro Desideri; Alzir A. Batista; Eliana A. Varanda (BioMetals, 2017)

C 2 ,N-dimethylbenzylamine cyclopalladated compounds: evaluation of cytotoxic, mutagenic and antitubercular activities - Antonio Carlos Moro; Gislaine Aparecida da Cunha; Ronan Farias Freire de Souza; Antonio Eduardo Mauro; Adelino Vieira de Godoy Netto; Iracilda Zepponi Carlos; Flávia Aparecida Resende; Eliana Aparecida Varanda; Fernando Rogério Pavan; Clarice Queico Fujimura Leite (Medicinal Chemistry Research, 2015)

Evolutionary and biogeographical approach on Australoheros angiru (Cichlidae) from lagoons in a dividing plateau between the basins of the Iguassu River and the Uruguay River, Brazil - Leonardo Marcel Paiz; Lucas Baumgartner; Rafaela Maria Moresco; Fernando Rodrigo Treco; Weferson Júnio da Graça; Vladimir Pavan Margarido (Reviews in Fish Biology and Fisheries, 2014)